2021
DOI: 10.3389/fonc.2021.630972
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Diets and Pancreatic Cancer: Molecular Mechanisms and Clinical Practice

Abstract: Pancreatic cancer (PC) is a malignant tumor with high invasiveness, easy metastatic ability, and chemoresistance. Patients with PC have an extremely low survival rate due to the difficulty in early diagnosis. It is estimated that nearly 90% of PC cases are caused by environmental risk factors. Approximately 50% of PC cases are induced by an unhealthy diet, which can be avoided. Given this large attribution to diet, numerous studies have assessed the relationship between various dietary factors and PC. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 195 publications
0
4
0
Order By: Relevance
“…In the context of PDA, while the KD has been shown to reduce pancreatic tumor growth in vivo in some models (Shukla et al , 2014), other studies revealed no effect of KD alone on PDA tumor growth or animal survival (Hopkins et al , 2018; Lien et al , 2021). Moreover, the limited number of PDA patients studied with this dietary intervention and the lack of long‐term follow‐up make the role of the KD in treating PDA patients unclear (Zhang et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of PDA, while the KD has been shown to reduce pancreatic tumor growth in vivo in some models (Shukla et al , 2014), other studies revealed no effect of KD alone on PDA tumor growth or animal survival (Hopkins et al , 2018; Lien et al , 2021). Moreover, the limited number of PDA patients studied with this dietary intervention and the lack of long‐term follow‐up make the role of the KD in treating PDA patients unclear (Zhang et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This dichotomy suggests that dietary FAω6 to FAω3 ratios may crucially influence inflammatory disease risks, including PC [ 36 ]. Some studies suggest that early life dietary patterns significantly impact cancer development [ 37 , 38 ]. The primary risk factors include a sedentary lifestyle and poor dietary choices, characterized by excessive intake of high-calorie foods and a lack of healthy foods such as those rich in FAω3, antioxidants, and fiber.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, healthy dietary habits, characterized by the consumption of fruits and vegetables rich in fiber, PUFAs, and vitamins, can positively impact human health by reducing chronic inflammation and subsequent DNA damage [ 41 , 42 ]. For example, adhering to a Mediterranean diet, which includes a high intake of fresh fruits, vegetables, legumes, unrefined grains, and olive oil, as well as higher nut consumption, has been shown to be associated with a lower risk of PC [ 38 , 40 ]. Additionally, the intake of PUFAs and their fish sources may have a protective effect against the development of PC.…”
Section: Discussionmentioning
confidence: 99%
“…Summarily, liver is the glucose and lipid metabolic center that produces ketone bodies, KD has a broad application prospect in the treatment of HCC ( 26 ). In addition, several recent studies have demonstrated that KD effectively inhibited the proliferation of pancreatic by reprogramming cell metabolism, epigenome, and the gut microbiome ( 27 , 28 ). These results suggested that glioma and breast cancer were the most studied cancer types in this field, while hepatocellular carcinoma and pancreatic cancer were the new hotspots and trends.…”
Section: Discussionmentioning
confidence: 99%